Low power software receiver for GPS L1/L5 - Toh, Ying Xuan (Nanyang Technological University, 2020)
This project is about the software platform development for signal demodulating of GPS L5 signals. The firmware involves C/Python language programming to implement the software GPS receiver blocks in ARM embedded platform. The report entails the details of a GPS system from acquisition to tracking and will provide an overall view on how a software receiver is beneficial in this field of study.